2022
DOI: 10.3390/nu14153090
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Viral Infections on Iron Homeostasis and the Potential for Lactoferrin as a Therapeutic in the Age of the SARS-CoV-2 Pandemic

Abstract: The association of hyperinflammation and hyperferritinemia with adverse outcomes in SARS-CoV-2-infected patients suggests an integral role for iron homeostasis in pathogenesis, a commonly described symptom of respiratory viral infections. This dysregulated iron homeostasis results in viral-induced lung injury, often lasting long after the acute viral infection; however, much remains to be understood mechanistically. Lactoferrin is a multipurpose glycoprotein with key immunomodulatory, antimicrobial, and antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Wotring et al 45 reported that bLf showed potent efficacy on different SARS‐CoV‐2 variants, but the underlying mechanisms were not explored. Ward et al 46 and Shafqat et al 47 summarized the role of Lf against SARS‐CoV‐2, including blocking viral attachment between HSPGs and viral particles and modulating the expression of immune‐related genes. Although most studies have demonstrated that Lf inhibits viral infection primarily by interfering with cell entry, few studies have suggested that the post‐infection addition of Lf could also reduce infection 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Wotring et al 45 reported that bLf showed potent efficacy on different SARS‐CoV‐2 variants, but the underlying mechanisms were not explored. Ward et al 46 and Shafqat et al 47 summarized the role of Lf against SARS‐CoV‐2, including blocking viral attachment between HSPGs and viral particles and modulating the expression of immune‐related genes. Although most studies have demonstrated that Lf inhibits viral infection primarily by interfering with cell entry, few studies have suggested that the post‐infection addition of Lf could also reduce infection 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, lipid damage catalyzed by iron overload can exert a direct causative effect on ferroptosis, which is more likely to amplify cell death and trigger a series of other inflammatory-related immune regulatory responses [61] (Figure 3). confirmed that levels of lactoferrin correlate with the severity of infectious pneumonia and sepsis induced by bacteria and viruses [12,66]. NRAMP1, as a divalent metal transporter and a vital player in the host-pathogen battle for phagolysosomal iron, may have a broader role in regulating macrophage iron homeostasis through the hepcidin-Nramp1 axis [67] (Figure 3).…”
Section: Direct Alimentioning
confidence: 73%
“…The microcytic anemia of the sla mouse was attributed to defective export of iron from enterocytes, indicating that decreased or defective hephaestin can lead to iron deficiency [ 7 – 9 ]. Infection of enterocytes with SARS-CoV-2 can induce down-regulation of ferroportin and hephaestin [ 10 ] and it was of interest to see if changes in serum hephaestin could correlate with COVID-19.…”
Section: Introductionmentioning
confidence: 99%